Synthesis and characterization of proton exchange poly (phenylenebenzophenone)s membranes grafted with propane sulfonic acid on pendant phenyl groups. (27th April 2017) - Sutradhar, Sabuj Chandra; Jang, Hohyoun; Banik, Nipa; Yoo, Jiho; Ryu, Taewook; Yang, Hanmo; Yoon, Sujin; Kim, Whangi
Abstract: A series of poly(phenylenebenzophenone)s with sulfonic acid groups via long alkyl side chains, SPPBPs, were successfully prepared as proton exchange membranes for fuel cells. The new monomer, 1, 4-dichloro-2, 5 diphenylenemethoxybenzophenone (PMBP) was synthesized by the Friedel–Crafts reaction of tetrachloroterephthalate with anisole and copolymerized with 1, 4-dichloro-2, 5-diphenylenebenzophenone (PBP) to prepare poly(phenylenebenzophenone)s copolymers containing dimethoxy groups (sPPMBP). After converting the methoxy group to the reactive hydroxyl group, the resulting side-chain-type sulfonated copolymers (SPPBP) were obtained by a sulfopropylation reaction. These SPPBP series membranes showed high proton conductivity in the range of 98.4–162.1 mS/cm 80 °C under 90% hydrated conditions. SPPBP-40 (IEC = 2.45 meq./g) showed comparable higher proton conductivity (162.1 mS/cm) than Nafion 211 (130.2 mS/cm) in the 90% hydrated state. The membranes were studied by 1 H NMR spectroscopy, thermo-gravimetric analysis, ionic exchange capacity, water uptake, and proton conductivity. Also surface morphologies were assessed by atomic force microscope (AFM). Highlights: We synthesized polymer electrolyte grafted with alkyl sulfonic acid groups. We controlled the degree of sulfonation by PMBP monomer. Increasing sulfonation level increases the proton conductivity. Membranes have the good performance with chemical stability and flexibility.